Food Logistics 4.0: Opportunities and challenges - Sandeep Jagtap; Farah Bader; Guillermo Garcia-Garcia; Hana Trollman; Tobi Fadiji; Konstantinos Salonitis (Logistics, 2021)
Food Logistics 4.0 is a term derived from Industry 4.0 focusing on all the aspects of food logistics management based on cyber-physical systems. It states that real-time information and the interconnectivity of things, supplemented with novel technologies will revolutionise and improve the way food logistics is carried out. It has tremendous potential in terms of bringing transparency, swift delivery of food at reduced cost, flexibility, and capability to deliver the right quality product at the right place and at the right time. This paper discusses the vital technologies within Food Logistics 4.0 and the opportunities and challenges in this regard. It focuses primarily on food logistics, including resource planning, warehouse management, transportation management, predictive maintenance, and data security. Internet of Things, Blockchain, Robotics and Automation and artificial intelligence are some of the technologies discussed.
Keywords: 650; additive manufacturing (3D printing); artificial intelligence; augmented reality; big data; Blockchain; cybersecurity; food logistics; Industry 4.0; internet of things; robotics and automation